2019
DOI: 10.7567/1347-4065/ab08ae
|View full text |Cite
|
Sign up to set email alerts
|

Selection of ion species suited for channeled implantation to be used in multi-epitaxial growth for SiC superjunction devices

Abstract: Recently, we found a mistake in the depth profile of channeled-ion implantation into 4H-SiC (0001), where 114-keV 27 Al ions were implanted at a dose of 1.3 × 10 13 cm −2 . However, the discussion of the manuscript is unchanged. We would like to apologize for any inconvenience.The sentence and figures related to the depth profile of channeled-ion implantation into 4H-SiC ( 0001), where 114-keV 27 Al ions were implanted at a dose of 1.3 × 10 13 cm −2 , written on page 050905-3 should be corrected as shown below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…21) In the case of channeling along the crystal axis, Se periodically fluctuates as a function of the atomic number of implanted ions. 14,22,26) Se is quite small in the case of channeling implantation for Al ion. Therefore, the profile of channeled Al ions becomes extremely deeper.…”
Section: Experimental Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…21) In the case of channeling along the crystal axis, Se periodically fluctuates as a function of the atomic number of implanted ions. 14,22,26) Se is quite small in the case of channeling implantation for Al ion. Therefore, the profile of channeled Al ions becomes extremely deeper.…”
Section: Experimental Methodsmentioning
confidence: 96%
“…Therefore, several studies have been reported on channeling implantation into 4H-SiC. [20][21][22] We also reported on channeling implantation of Al and P ions into 4H-SiC at the Solid State Devices and Manufacturing (SSDM) 2021. 23) Especially, we found that the abrupt deep profile can be formed by channeling implantation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Every Si (or C) atom is tetrahedrally surrounded by four C (or Si) atoms, and the stacking sequence of double layers (consisting of a Si layer and a C layer) along the [0001] direction is A, B, C, and B; namely, with regard to the double layer B, the adjacent double layers (A and C) shift. The symmetric structure has promoted the study of channeled-ion implantation of p-type dopants into (0001) 4H-SiC [7][8][9][10][11][12] for fabricating super-junction (SJ) devices. 13,14) This is because SJ devices require box-like acceptor profiles.…”
mentioning
confidence: 99%
“…However, even for implantations 4° off from the [000-1] direction, some ions will be steered into crystal channels and these ions will contribute to a deep tail in the dopant distribution [7]. In SiC, the channeled ions may come to rest significantly deeper than the projected range of an amorphous target [4][5][6][7][8][9]. The degree of channeling varies with atomic number of implanted ions as well as the energies used.…”
Section: Introductionmentioning
confidence: 99%
“…This is expected to result in an almost Gaussian shaped depth profile. If the implantation is instead performed along a major crystal axis, the ions will follow the crystal direction substantially deeper into the crystal [1][2][3] and the concentration versus depth profile will have a broader distribution [4][5][6]. However, even for implantations 4° off from the [000-1] direction, some ions will be steered into crystal channels and these ions will contribute to a deep tail in the dopant distribution [7].…”
Section: Introductionmentioning
confidence: 99%